METACOGNITIVE AWARENESS AND TEACHING COMPETENCE AMONG STUDENT-TEACHERS IN SOUTHWESTERN NIGERIA - Okunola, Gloria Aghogho; Adeniyi, Wasiu Olasunkanmi; Ghozali, Muhamad Afifuddin; Purwoko, Budi (Jurusan Bimbingan dan Konseling, 2025)
This study examines the level of metacognitive awareness of faculty of education undergraduate student-teachers on the field for teaching practice exercise and also determine the influence of metacognitive awareness on academic competence among undergraduate student-teachers in Southwestern Nigeria. With the increasing recognition of metacognition as a core determinant of student success, this research sought to analyse how well student-teachers regulate and reflect upon their learning processes. A total of 120 student-teachers from four public universities in southwestern Nigeria were selected through a multistage sampling technique. Using validated instruments; the Teacher Competence Assessment Scale (TCAS) and the Metacognitive Awareness Scale (MAS), the study employed descriptive statistics and regression analysis to measure the levels of metacognitive awareness and their predictive capacity on teaching competence. Findings revealed that the majority of student-teachers exhibited moderate levels of metacognitive awareness. However, the regression analysis showed no significant influence of metacognitive awareness on teaching competence. These results have implications for teacher education programs and the integration of metacognitive strategy instruction